Solid organ transplantation in the 21st century - Black, Cara K.; Termanini, Kareem M.; Aguirre, Oswaldo; Hawksworth, Jason S.; Sosin, Michael (Annals of Translational Medicine; Vol 6, No 20 (October 26, 2018): Annals of Translational Medicine, 2018)
Solid organ transplantation (SOT) has emerged from an experimental approach in the 20th century to now being an established and practical definitive treatment option for patients with end-organ dysfunction. The evolution of SOT has seen the field progress rapidly over the past few decades with incorporation of a variety of solid organs—liver, kidney, pancreas, heart, and lung—into the donor pool. New advancements in surgical technique have allowed for more efficient and refined multi-organ procurements with minimal complications and decreased ischemic injury events. Additionally, immunosuppression therapy has also seen advancements with the expansion of immunosuppressive protocols to dampen the host immune response and improve short and long-term graft survival. However, the field of SOT faces new barriers, most importantly the expanding demand for SOT that is outpacing the current supply. Allocation protocols have been developed in an attempt to address these concerns. Other avenues for SOT are also being explored to increase the donor pool, including split-liver donor transplants, islet cell implantation for pancreas transplants, and xenotransplantation. The future of SOT is bright with exciting new research being explored to overcome current obstacles.